An implementation of toll road smart lamps as Indonesia's green energy solution - Hermansyah Alam; Zulfadli Pelawi; Mahrizal Masri (SEAN Institute, 2024)
The Lighting is very much needed in various areas of life today, both for individuals and the living environment. Considering that roads are places that we always pass, this requires lighting in various sectors, including steep roads that must be equipped with maximum lighting. We often know that many accidents occur, one of which is caused by the lack of lighting on the side of the road. Seeing this and considering technological developments, an intelligent system based on Arduino UNO was created which was able to overcome this problem. With Arduino UNO, LDR Light Sensor, and IR Sensor, this intelligent system is able to turn on the lights automatically for road users, thus this tool will be able to reduce the problem of accidents that often occur on the road, and is also able to provide a sense of security and comfort for drivers.